ANALISIS PENGARUH PRODUK, HARGA, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN RUMAH ( Studi pada Perumahan Graha Estetika Semarang ) - Widyasari, Suzy; Triastuti Fifilia, Erna (Jurnal Ilmiah Telaah Manajemen, 2009)
Housing is the oneof basic needs that people want. As the raising amount of population, the demand of this product also tend to increase. This fenomena is being an interesting opportunities for businessmen,especially for developers who supply housing as their product. For those, consumers will be faced with many kinds of product housing’s supplies to fulfill their need of housing as the home living. Related to the fact, thisstudy try to analize the influence of product, price, promotion and location to buying decision making of product housing at Graha Estetika Housing in Semarang. There were five hipothesis tested in this study byusing multiple linier regression. Convenience sampling is a method that used in this research to get the respondent as samples. The result show that there were got positive significant effects of product, price,promotion and location to buying decision making of product housing at Graha Estetika Housing in Semarang both as partially and simultanly.Key words: Product, Price, Promotion, Location, Buying decision making.